D'Hancarville's useful history. Issue 3 (3rd July 2017) - Mack, Ruth
Abstract: Pierre-François Hugues, the self-styled Baron d'Hancarville, begins his Collection of Etruscan, Greek, and Roman Antiquities from the Cabinet of the Hon. W. Hamilton (Naples, 1766–76) by acknowledging the text's antiquarian aims, even as he points his project toward the artisan's workshop, fully embracing its future role as a pattern book. This essay argues that these two missions—antiquarian and artisanal—are not as far apart as they might seem and that d'Hancarville offers us the means to understand their relation through his empiricist account of perception. In both written text and images, he leads the reader through a theory of practical, useful knowledge and, ultimately, shows us how such practice is a fundamental part of our ability to apprehend the past in the present.